Managerial Questions of Human Resource Management in Agriculture - Berde, Csaba (Acta Agraria Debreceniensis, 2003)
Human resource management has many charasteristics in the field of agriculture, which should be taken into consideration from the point of view of management. Becoming a farmer is a result of a socializational process, in which tradition has a determining role. The ratio of unqualified labour in agriculture is high, compared to other sectors, and the situation is similar considering age. The number of employees is continuously decreasing; and this kind of work is determined by seasonality. Fluctuation is high, and methods for evaluating production are not well accepted. Managerial expectations changed considering labour. According to experimental results, the importance of qualification has decreased, while suiting a specific job and its duties has become more important.